Cytological studies reveal high variation in ascospore number and shape and conidia produced directly from ascospores in Morchella galilaea - Du, Xi-Hui; Wang, Si-Yue; Ryberg, Martin; Guo, Yong-Jie; Wei, Jing-Yi; Pfister, Donald H.; Johannesson, Hanna (Frontiers in Microbiology, 2023)
Spores are important as dispersal and survival propagules in fungi. In this study we investigated the variation in number, shape, size and germination mode of ascospores in Morchella galilaea, the only species of the genus Morchella known to fruit in the autumn. Based on the observation of five samples, we first discovered significant variation in the shape and size of ascospores in Morchella. One to sixteen ascospores were found in the asci. Ascospore size correlated negatively with ascospore number, but positively with ascus size, and ascus size was positively correlated with ascospore number. We noted that ascospores, both from fresh collections and dried specimens, germinated terminally or laterally either by extended germ tubes, or via the production of conidia that were formed directly from ascospores at one, two or multiple sites. The direct formation of conidia from ascospores takes place within asci or after ascospores are discharged. Using laser confocal microscopy, we recorded the number of nuclei in ascospores and in conidia produced from ascospores. In most ascospores of M. galilaea, several nuclei were observed, as is typical of species of Morchella. However, nuclear number varied from zero to around 20 in this species, and larger ascospores harbored more nuclei. One to six nuclei were present in the conidia. Nuclear migration from ascospores to conidia was observed. Conidia forming directly from ascospores has been observed in few species of Pezizomycetes; this is the first report of the phenomenon in Morchella species. Morphological and molecular data show that conidial formation from ascospores is not found in all the specimens of this species and, hence, is not an informative taxonomic character in M. galilaea. Our data suggest that conidia produced from ascospores and successive mitosis within the ascus may contribute to asci with more than eight spores. The absence of mitosis and/or nuclear degeneration, as well as cytokinesis defect, likely results in asci with fewer than eight ascospores. This study provides new insights into the poorly understood life cycle of Morchella species and more broadly improves knowledge of conidia formation and reproductive strategies in Pezizomycetes.